Problem Based Learning in Basic Physics -VIII - A. K. Mody; H. C. Pradhan (SCHOOL SCIENCE, 2015)
In this article, seventh in the series of articles, we present problems for a problem based learning course from the area of material properties. We present the learning objectives in this area of basic physics and what each problem tries to achieve with its solution. methodology and philosophy of selecting these problems have already been discussed. (Pradhan 2009, ody 2011) To review methodology in brief, we note here that this PBL (problem based learning) starts after students have been introduced to formal structure of physics. Ideally, students would attempt only the main problem. If they find it difficult, then depending upon their area of difficulty, right auxiliary problem have to be introduced by a teacher who is expected to be a constructivist facilitator. The teacher may choose as per his/her requirement or may construct questions on the sp